Pemberdayaan Ekonomi Masyarakat Melalui Pemanfatan Bambu di Kabupaten Soppeng - Asrar Fadly Mubarak; Irwan Misbach; Irwanti Said (Jurnal Berita Sosial, 2023)
This research aims to describe the form of economic empowerment through bamboo utilization in Soppeng Regency. In addition, to find out the obstacles experienced by the community in empowering the community’s economy through the use of bamboo in Soppeng Regency. In the explanation of this journal, the type of research used is descriptive qualitative research using a sociological economist approach to see how the community’s economic empowerment through the use of bamboo plants, as well as through various series of activities such as observations, interviews, literature studies and documentation. While the data analysis used is data reduction, data presentation and conclusion drawing. The results of this study indicate that: a form of economic empowerment through the use of bamboo in Soppeng Regency is through selling in the form of whole bamboo, then also through selling bamboo in the form of Salima (bamboo split). The obstacles experienced in empowering the community’s economy through the use of bamboo in Soppeng Regency are road access that is difficult to take, uncertain selling prices of bamboo, unfavorable weather.